PROBLEMATIKA SOSIAL PENERAPAN HUKUM ISLAM DI INDONESIA - Norcahyono Norcahyono (JURIS (Jurnal Ilmiah Syariah), 2019)
The application of Islamic law in Indonesia has experienced obstacles since the entry of Western law into Indonesia. So that legal theories were born in response to friction between Western law with Islamic law. Receptie theory emerged as a Dutch strategy for corner and reduce Islamic law in Indonesia. Then, the coming of the theory of Receptie Exit law and Receptio a Contrario legal theory as symbols of resistance to prove that Islamic law still exists in Indonesia. There are two social problems which has a big influence on the application of Islamic law in Indonesia; First: the entry of Western law into Indonesia which intersects with Customary law. Second: Political and cultural influences of the community. In sociological reviews, Islamic law is difficult to be applied in Indonesia, because Islamic law is existed in the area of Religion to territory of the country.